To repeat or not to repeat: Radiologists demonstrated more decisiveness than their fellow radiographers in reducing the repeat rate during mobile chest radiography. Issue 2 (May 2021) - Saade, C.; Siblini, L.; Karout, L.; Khalife, S.; Hilal, H.; Abbas, S.; Salman, R.; Naffaa, L.
Abstract: Introduction: Radiologists and radiographers play a complementary role in providing an optimal image quality with decrease radiation dose and proper diagnosis during chest radiographs. We aim Investigate years of experience among radiologists and radiographers on perception of image quality and its impact on repeat rate when evaluating portable pediatric chest radiographs. Methods: IRB approved retrospective study consisted of randomly selected images (n = 131) of pediatric portable chest radiographs. Images were blindly assessed by four radiologists and four radiographers. Readers were asked to assess qualitative and quantitative image quality by rating: image quality, decision to repeat and image technique. All data was compared employing Pearson's Correlation, Visual grading characteristic (VGC) and Cohens' kappa analyses. Results: Image quality: Radiologists (88.4%) rated images as excellent significantly more than radiographers (11.6%), and radiographers (90.1%) as poor significantly more than radiologists (9.9%) (p < 0.05). Repeat: Radiologists (57%) decided not to repeat images significantly more than radiographers (43%) (p < 0.05). Image technique: Radiologists rated images as acceptable (65%) and excellent (97.7%) significantly more than radiographers (35% and 2.3% respectively) (p < 0.05), whereas radiographers (84%) assessed image technique as poor significantly more than radiologists (16%) (p < 0.05). VGC: radiographers had slightly better qualitative evaluation of image quality than radiologists. An association between image quality (p < 0.002) and repeat decision (p < 0.044) with years of experience was established when comparing years of experience with image assessment rubric, while no association was noted with image technique (p < 0.9). Conclusion: Radiologists demonstrated more decisiveness than their fellow radiographers in reducing the repeat rate of portable pediatric chest radiographs. Interestingly, years of experience only seem to affect image technique and image quality assessment among radiologists. Implications for practice: Continuous education of radiographers and close collaboration with radiologists is crucial to achieve optimal image quality and low radiation doses.